2012
DOI: 10.9753/icce.v33.structures.81
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Tsunami-Induced Hydrodynamic Forces on Onshore Structures Using SPH

Abstract: In this paper, the simulation of the violent impact of tsunami-like bores with a square column is performed using a single-phase, weakly compressible three-dimensional Smoothed Particle Hydrodynamics (SPH) model. In order to avoid large fluctuations in the pressure field and to obtain accurate simulations of the hydrodynamic forces, a Riemann solver-based formulation of the SPH method is utilized. Large-scale physical experiments conducted by the authors are reproduced using the numerical model. Time-histories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…The interested flow regime in the present study is turbulent, whereas most of the existing IB methods are limited to low to moderate Reynolds numbers [73,74] with few exceptions [75]. Moreover, at high Reynolds numbers, mass and momentum conservation becomes important [72]. The continuous and discrete forcing methods may suffer from poor mass conservation [76] since none of them are designed to satisfy the conservation laws [71].…”
Section: Immersed Boundary Methods With Cut-cell Techniquementioning
confidence: 98%
See 1 more Smart Citation
“…The interested flow regime in the present study is turbulent, whereas most of the existing IB methods are limited to low to moderate Reynolds numbers [73,74] with few exceptions [75]. Moreover, at high Reynolds numbers, mass and momentum conservation becomes important [72]. The continuous and discrete forcing methods may suffer from poor mass conservation [76] since none of them are designed to satisfy the conservation laws [71].…”
Section: Immersed Boundary Methods With Cut-cell Techniquementioning
confidence: 98%
“…The boundary forces can be added to the continuous [31] or discretized [71] Navier-Stokes equations. The discrete forcing method does not impose additional stability constraints in the boundary representation and enables a sharper interface representation [71,72]. Detailed reviews of various IB methods can be found in Huang and Tian [73], Kajishima and Taira [72], Kim and Choi [74], and Mittal and Iaccarino [71].…”
Section: Immersed Boundary Methods With Cut-cell Techniquementioning
confidence: 99%
“…To validate the numerical approach, the experimental and numerical model of St-Germain et al (2012) was reproduced, comparing water elevations of the incident wave in two control gauges. A tank 13.17 m long, 2.7 m wide, divided into two sections, and 1.4 m in height (Fig.…”
Section: Validationmentioning
confidence: 99%
“…For the SPH method, the particles move in Lagrangian coordinates and the advection is directly calculated by particle motion without numerical diffusion [9]. As SPH is a type of mesh-free method, it is inherently suitable for solving the procedures of moving discontinuities with large deformations [3], and it has been utilized to resolve a wide range of hydrodynamics problems [10][11][12][13]. Rafiee et al [14] used the pressure Poisson equation in the SPH method to solve the incompressible problem of fluid, and verified that the method can well simulate the dynamic response between the free surface of fluid and the structure; Dao et al [15] established a numerical wave flume based on SPH method, which was successfully applied to simulate the cases of tsunami wave propagating on the slope and wave impacting on coastal structures; and St-Germain et al [16] used the weak compressibility SPH method to compute the wave force of the rapidly developing tsunami wave acting on the square cylinder, and the computed results fit well with the results of large-scale physical experiments.…”
Section: Introductionmentioning
confidence: 99%